Herbage mass of Teosinte (Euchlaena mexicana) grown as mono and mixed with legumes (Bangladesh Journal of Animal Science, 2022)
The popular summer cereal fodder is Teosinte (Euchlaena mexicana) which has low productivity and chemical constituents. The quality and quantity of teosinte fodder can be enhanced by adjusting cultivation practices including use of appropriate sowing dates and by following an appropriate mixed cropping cultivation with legumes. This study was conducted to identify the fodder quantity and quality under a commonly practiced mixed cultivation of legumes with teosinte with varied sowing dates. Three combination of fodder; teosinte, teosinte+cowpea and tesosinte+rice bean was arranged in four sowing dates in Split Plot Design, replicated five times. Sowing dates were arranged as main plot while combination of fodder species was arranged as sub plot. Growth parameters of teosinte (tiller numbers/m2, plant height), green herbage mass, dry herbage mass, crude protein (CP), acid detergent fiber (ADF) and neutral detergent fiber (NDF) were determined. The results showed significantly highest (p